2019
DOI: 10.32479/ijeep.7476
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oil and Non-Oil Exports on Economic Growth in Bahrain

Abstract: This study investigates the effect of oil and non-oil exports on economic growth in Bahrain over the period 1977-2015. The cointegration analysis shows that economic growth was positively and significantly related to exports. However, oil effects have the biggest effect on real gross domestic product. Also, results show that oil exports have a positive impact on economic growth both in the short run and in the long run. Therefore, further encouragement of non-oil sectors and higher diversification of exports w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
(19 reference statements)
2
6
0
2
Order By: Relevance
“…The study revealed a negative relationship between oil exports and economic growth while a positive relationship was found between non-oil exports and economic growth. A similar finding was reported by Khayati (2019) in Bahrain for non-oil export and economic growth. However, the study reported a positive impact between oil export and economic growth contradicting the findings by Raheem (2016).…”
Section: Empirical Reviewsupporting
confidence: 89%
“…The study revealed a negative relationship between oil exports and economic growth while a positive relationship was found between non-oil exports and economic growth. A similar finding was reported by Khayati (2019) in Bahrain for non-oil export and economic growth. However, the study reported a positive impact between oil export and economic growth contradicting the findings by Raheem (2016).…”
Section: Empirical Reviewsupporting
confidence: 89%
“…For small emerging economies, oil and natural gas play a dominant role in Bahrain's economy. In 2017, some 19% of its GDP was contributed by this sector (Khayati, 2019). The country's banking and financial services have also benefited from the regional boom driven by demand for oil (Alaali & Naser, 2020); the financial sector contributed to almost 17% of the national GDP in 2017 (source: Ministry of Finance, Bahrain).…”
Section: Value‐added Account Validationmentioning
confidence: 99%
“…This study has revealed important findings of testing the variability in export revenues as an average of OECD countries in recent years with an important econometric model. In addition, it appears that Khayati's (2019) article on the relationship between exports and economic growth, published, reveals meaningful determinations for OECD countries. In this article, significant findings have been made about which scales of impact on energy exports will affect growth, especially in the scope of the OECD.…”
Section: Literature Reviewmentioning
confidence: 99%